The causes and effect of delay in construction industry project - Intan Diana, Musa (2012)
The most common problems in the construction project is delays, it's very linked to each other. Delays of a construction project can be defined as the late completion of works as compared to the planned schedule or contract schedule. Projects can be delayed due to number of reasons that may be due to the client, the contractor, acts of God, or a third party. They may occur early or later in the project development, alone, or with other delays. Delays can be minimized only when their cause are identified. The objective of this study was to identify the major causes of construction delays and the effects of delays construction delays. This study was carried out based on literature review and a questionnaire survey. A total of eight causes were contributed to the cause of construction delays and six factors that effects construction delays were identified based on literature review. From the survey, this study presents the results of a survey undertaken to determine and evaluate the most frequent factors causing delay construction projects. A survey based on a questionnaire was distributed out among randomly selected contractors, consultants, and owners. The main causes of delay are analyzed and ranked according to their frequency of occurrence. The objectives of the study have been successfully achieved based on the results of the study. The most important factors that contributed to the causes of delays, for example, insufficient numbers of equipment, changes orders, poor site management and supervision, shortage of construction materials, incompetent project team, improper project planning and scheduling, and contractor's financial difficulties. Management factors was ranked the most significant cause delays, followed by economy factors, manpower factors, site factors, contractual factors and external factors. Time and cost overrun were the common effects of delays in construction projects